الاقتصاد العربي والنفط - قنوع نزار; سطايحي هيثم; صيوح لؤي (Latakia University Journal - Economic and Legal Sciences Series, 2019)
سوف نتناول في هذا البحث تنامي دور القطاع النفطي في الاقتصاد العربي منذ منتصف السبعينيات وأسباب ضعف الاقتصاد العربي، والتحديات التي تواجهها الاقتصادات العربية, لاسيما بعد احتلال العراق وسرقة ثرواته الباطنية، وطرح مشروع الشرق الأوسط الكبير. واعتماد معظم هذه الاقتصادات على القطاع الخارجي، وارتباطها العضوي مع السوق العالمية وتكاملها الدولي في حقول الإنتاج والتبادل والاستثمار والتكنولوجيا وذلك على حساب التكامل العربي: إذ لا بد من التصدي لهذه التحديات بعقلانية وتفاعل مثمر لتقليل أضرارها وتعظيم منافعها وتفعيل دور الجامعة العربية من خلال تطوير النظام الاقتصادي العربي، وإعطاء النفط الدور الإيجابي في تحقيق الإنجازات التي تتلائم مع القدرات العربية. والتقدم خطوة خطوة للوصول إلى السوق العربية المشتركة المرجوة. We will deal in this research with some major issues regarding the increasing role of oil sector in the Arab Economy since the mid seventieth and the main reasons of its weakness. The challenges facing our economies especially after the occupation of Iraq, stealing its fortunes and presenting the broad middle East project. Thje paper also takes into consideration how many Arab economies are deeply related and relied on foreign sector, and how well they connect with the international market in different fields (production, trade, investment, technology) preferring the international integration to the Arabic one. It is important to realize how much the rational thinking and dealing with these challenges is important to minimize the damages and to increase the benefits. Arab league needs to have an active role developing the Arab economy, giving the oil its positive role and moving forward to build common Arab market.